Role of large language models in the multidisciplinary decision-making process for patients with renal cell carcinoma: a pilot experience - Riccardo Bertolo; Lorenzo De Bon; Filippo Caudana; Greta Pettenuzzo; Sarah Malandra; Chiara Casolani; Andrea Zivi; Emanuela Fantinel; Alessandro Borsato; Riccardo Negrelli; Emiliano Salah El Din Tantawy; Giulia Volpi; et al. (npj Precision Oncology)
Abstract We evaluated an AI chatbot’s ability to suggest diagnostic and therapeutic pathways for renal cell carcinoma (RCC) in a multidisciplinary tumor board (MDT). A retrospective analysis of 103 cases (2023–2024) found 62.1% agreement with MDT decisions (κ = 0.44, p< 0.001). Concordance was highest in when follow-up imaging was suggested (p = 0.001), with disease status influencing agreement (p = 0.004). These results suggest AI could assist in RCC case assessments, warranting further research.